2015
DOI: 10.2500/aap.2015.36.3815
|View full text |Cite
|
Sign up to set email alerts
|

IgE reactivity to carbohydrate moieties of glycoproteins in wheat allergy

Abstract: Carbohydrate moieties of different glycoproteins, such as cross-reactive carbohydrate determinants (CCDs) and galactose α-1,3-galactose, can induce IgE reactivity with varied clinical significance. In this study, the possible participation of glycan from wheat gliadin, with respect to its IgE-binding capacity, was investigated in children with food allergies to wheat. Total IgE and wheat-specific IgE quantification, documentation of history, and/or oral food challenge (OFC) were performed for 52 children. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…By contrast to the previous findings, in humans the presence of IgE against galactose‐α‐1,3‐galactose in red meat was reported to result in severe clinical reactions . Another study showed that IgE against gliadin in wheat led to greater allergenicity in wheat‐allergic symptomatic children compared to nonexposed or asymptomatic individuals, implying that the assumption that those antibodies have no clinical impact is not applicable for all CCDs. In the dog, the presence of anti‐CCD IgE did not lead to polysensitization with IDT, which may indicate that they are clinically irrelevant in canine AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast to the previous findings, in humans the presence of IgE against galactose‐α‐1,3‐galactose in red meat was reported to result in severe clinical reactions . Another study showed that IgE against gliadin in wheat led to greater allergenicity in wheat‐allergic symptomatic children compared to nonexposed or asymptomatic individuals, implying that the assumption that those antibodies have no clinical impact is not applicable for all CCDs. In the dog, the presence of anti‐CCD IgE did not lead to polysensitization with IDT, which may indicate that they are clinically irrelevant in canine AD.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, specific IgE against these glycoproteins has been reported and these anti‐CCD IgE antibodies are believed to be a cause of positive in vitro test results . Anti‐CCD IgE antibodies against CCDs in plants and insects for the most part do not seem to have clinical relevance, although notable exceptions such as galactose‐α‐1,3‐galactose in red meat and glycan in wheat have been reported . One possible reason for the inability to cause clinical symptoms is the monovalent structure of the CCDs, preventing cross‐linking and mast cell degranulation …”
Section: Introductionmentioning
confidence: 99%
“…The size, solubility, and stability ensure protein transport and survival, whereas glycation may affect stability and immunogenicity (Shreffler et al 2006, Ilchmann et al 2010, Song et al 2015. For instance, the carbohydrate moiety of peanut vicilin is involved in dendritic cell activation and T H 2 cell maturation (Shreffler et al 2006).…”
Section: Nature Of Food Allergensmentioning
confidence: 98%
“…These asthmatic patients who also manifest the symptoms of COPD are diagnosed with asthma-COPD overlap syndrome (ACOS). 3,4 Meanwhile, patients with COPD with good obstruction reversibility, whereas increased eosinophil counts, can also be classified as ACOS. 5 Most ACOS patients are elderly and manifest the symptoms of both asthma and COPD.…”
Section: Introductionmentioning
confidence: 99%